Rediscovery of the enigmatic fungus-farming ant Mycetosoritis asper Mayr (Hymenoptera: Formicidae): Implications for taxonomy, phylogeny, and the evolution of agriculture in ants - Sosa-Calvo, Jeffrey; Jesovnik, Ana; Vasconcelos, Heraldo L.; Bacci, Mauricio [UNESP]; Schultz, Ted R. (Public Library Science, 2017)
We report the rediscovery of the exceedingly rarely collected and enigmatic fungus-farming ant species Mycetosoritis asper. Since the description of the type specimen in 1887, only four additional specimens are known to have been added to the world's insect collections. Its biology is entirely unknown and its phylogenetic position within the fungus-farming ants has remained puzzling due to its aberrant morphology. In 2014 we excavated and collected twenty-one colonies of M. asper in the Floresta Nacional de Chapeco A in Santa Catarina, Brazil. We describe here for the first time the male and larva of the species and complement the previous descriptions of both the queen and the worker. We describe, also for the first time, M. asper biology, nest architecture, and colony demographics, and identify its fungal cultivar. Molecular phylogenetic analyses indicate that both M. asper and M. clorindae are members of the genus Cyphomyrmex, which we show to be paraphyletic as currently defined. More precisely, M. asper is a member of the Cyphomyrmex strigatus group, which we also show to be paraphyletic with respect to the genus Mycetophylax. Based on these results, and in the interest of taxonomic stability, we transfer the species M. asper, M. clorindae, and all members of the C. strigatus group to the genus Mycetophylax, the oldest available name for this clade. Based on ITS sequence data, Mycetophylax asper practices lower agriculture, cultivating a fungal species that belongs to lower-attine fungal Clade 2, subclade F.